Evaluation of the Hepatoprotective Effects of Vitex negundo and Hygrophila auriculata in D-Galactosamine-Induced Liver Injury in Rats - Khantal, Anjali; Bais, Nidhi (Journal of Neonatal Surgery, 2025)
Liver diseases remain a major global health concern, often driven by oxidative stress, inflammation, and metabolic disturbances. This study investigates the hepatoprotective properties of Vitex negundo Linn and Hygrophila auriculata in a D-galactosamine (D-GalN)-induced hepatotoxicity model using Wistar rats. Ethanolic extracts of both plants were administered orally at a dose of 200 mg/kg for 14 days. Hepatic injury was induced via intraperitoneal injection of D-GalN (400 mg/kg), with silymarin (100 mg/kg) employed as a standard reference drug. Biochemical assessments revealed that treatment with V. negundo and H. auriculata significantly reduced serum levels of ALT, AST, ALP, and bilirubin compared to the toxic control group. Notably, ALT levels decreased to 42 ± 5 U/L and 45 ± 7 U/L in the V. negundo and H. auriculata groups, respectively, versus 120 ± 10 U/L in the toxic control. Antioxidant assays indicated a restoration of superoxide dismutase (SOD) and catalase (CAT) activity, along with a marked reduction in malondialdehyde (MDA) levels—dropping from 4.8 ± 0.6 nmol/mg (toxic control) to 1.5 ± 0.4 nmol/mg and 1.6 ± 0.5 nmol/mg in the extract-treated groups. Histopathological analysis corroborated these findings, showing improved liver architecture in treated rats. Overall, the results suggest that Vitex negundo and Hygrophila auriculata exert significant hepatoprotective effects and hold promise as potential therapeutic agents for the management of liver disorders.